Two-color immunofluorescence and flow cytometric analysis of lamina propria lymphocyte subsets in ulcerative colitis and Crohn's disease. - Senju, M; Wu, K; Mahida, Y; Jewell, D (Kluwer Academic Publishers-Plenum Publishers, 1991)
By using two-color immunofluorescence with fluorescein isothiocyanate (FITC) and phycoerythrin (PE)-labelled monoclonal antibodies and multiparameter flow cytometry, we investigated lamina propria lymphocyte subsets of patients with ulcerative colitis (UC) and Crohn's disease (CD). Leu-3/Leu-2 (CD4/CD8) ratio of lamina propria lymphocytes (LPL) of CD (mean +/- SD: 1.9 +/- 0.8, P less than 0.01) was significantly decreased compared with controls (3.3 +/- 1.1), because of an increased number of CD8+ lymphocytes. The majority of lamina propria CD4+ cells were CD4+, Leu-8- and CD4+, CD45R- both in controls and IBD tissue. Many lamina propria T lymphocytes were activated, expressing HLA-DR antigen not only in IBD but also in controls. NK cells defined by CD16 and CD 56 (3.0 +/- 1.4%, P less than 0.01) were significantly decreased in patients with UC compared with controls (6.5 +/- 3.0%). A low proportion of B cells in the intestinal mucosa expressed Leu-8 antigen and CD23 antigen. The proportion of activated B cells of LPL was high in IBD mucosa as well as normal mucosa. These findings suggest that local activation of B cells leads to the loss of the expression of Leu-8 antigen and CD23.